Rekonstruksi Filsafat Pendidikan Mohammad Sjafei: Analisis Ontologi, Epistemologi, dan Aksiologi Serta Relevansinya dalam Kurikulum Merdeka - Meri Erlina; Erlina Wiyanarti (Jurnal Artefak, 2026)
Contemporary Indonesian education faces the challenge of producing graduates who are intellectually competent while rooted in national values. However, systematic philosophical reconstruction of national education thinkers as a foundation for the Merdeka Curriculum remains limited. This study aims to reconstruct Mohammad Sjafei’s educational philosophy through ontological, epistemological, and axiological analysis, map its position within pragmatism, essentialism, and progressivism, and identify its relevance to history learning. The study employed a qualitative method using a philosophical-historical literature approach and conceptual content analysis of Sjafei’s works and authoritative secondary sources. The findings reveal that Sjafei’s educational philosophy is grounded in the concept of integral humanity, contextual experience, and national character formation, reflected in the principle of “Alam Terkembang Jadi Guru” and the active-creative educational system of INS Kayutanam. The study contributes a synthesis of Western educational philosophy and local Indonesian epistemology as a reconstructive framework for place-based history pedagogy and strengthening the Pancasila Student Profile.